(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2006)
We consider it a primary precondition to abandon the use of centrifugal spreaders. Since agricultural technology requires multiple application of low fertiliser rations, we investigated the use of the ATD-2 batcher . It turned out that these batchers could not ensure spreading of small rations. In search of an alternative solution we chose reel-type seed distributors. Experiments showed that such a design ensures uniform distribution with the use of upper sowing at the required rate of 20 g/m2. By sowing in this way, the granules are exposed to minimum damage. The spreader of this type is mounted upon the strawberry inter-row cultivation unit KIZ-3. It is a multipurpose unit that allows cultivating row-spacings, cutting off tendrils and loosening the cultivated soil. Research was carried out in the placement of mineral fertilisers in the soil. A rate was recognised as an optimum when the fertilisers were applied at the depth of 2-3 cm and 7 cm apart from the centre of the strawberry plant on both its sides. An important condition is that the composition of mineral fertilisers should meet the requirements of agricultural technology, they should be dry and not cloggy. The technology applied gives a great economic effect as well. The economy of fertilising means alone adds up to 20-45 Ls/ha.